2022
DOI: 10.1002/glia.24251
|View full text |Cite
|
Sign up to set email alerts
|

Piezo channels contribute to the regulation of myelination in Schwann cells

Abstract: Peripheral nerves and Schwann cells have to sustain constant mechanical constraints, caused by developmental growth as well as stretches associated with movements of the limbs and mechanical compressions from daily activities. In Schwann cells, signaling molecules sensitive to stiffness or stretch of the extracellular matrix, such as YAP/TAZ, have been shown to be critical for Schwann cell development and peripheral nerve regeneration. YAP/TAZ have also been suggested to contribute to tumorigenesis, neuropathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 76 publications
(130 reference statements)
1
33
0
Order By: Relevance
“…Transcriptional regulator YAP senses and responds to mechanical change through nuclear translocation, and its nuclear activation promotes cell proliferation. Piezo1 has been reported to regulate YAP activation in Schwann cells, another type of glial cells in the nervous system (Acheta et al, 2022). Therefore, we focused on the YAP to explore the mechanism involving Piezo1‐loss‐induced cell cycle arrest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional regulator YAP senses and responds to mechanical change through nuclear translocation, and its nuclear activation promotes cell proliferation. Piezo1 has been reported to regulate YAP activation in Schwann cells, another type of glial cells in the nervous system (Acheta et al, 2022). Therefore, we focused on the YAP to explore the mechanism involving Piezo1‐loss‐induced cell cycle arrest.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Piezo1 promotes concerted activation of NFATc1, YAP1, and β‐catenin transcription factors to facilitate osteoblast differentiation during bone development (Zhou et al, 2020). Moreover, Piezo1 regulated YAP/TAZ activation in Schwann cells and contributed to myelin development in the peripheral nervous system (Acheta et al, 2022). Based on our study, The mechanosensitive transcription factor YAP is closely associated with the function of Piezo1, and the Piezo1‐YAP signaling contributes to ONH astrocytes proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Piezo1 is an inhibitor of Piezo2 (Acheta et al, 2022). In addition, Piezo1 and Piezo2 are both robustly expressed in articular chondrocytes, synergistically promoting mechanically mediated Ca 2+ signaling in chondrocytes and promoting mechanical strain-mediated cell damage following injury (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that Piezo1 is a negative regulator of myelin formation in oligodendrocytes and Schwann cells (Acheta et al, 2022;Li et al, 2021;. Piezo1 is highly active after axonal injury and during axonal regeneration (Segel et al, 2019;, which may exacerbate nerve dam- et al, 2022).…”
Section: Studymentioning
confidence: 99%
“…It showed that both Piezo1 and Piezo2 are highly expressed in Schwann cells, but they have different roles in myelination. Piezo1 inhibits radial and longitudinal myelination while Piezo2 is required for myelin formation in the peripheral nervous system (PNS) ( 72 ). But whether Piezo2 is involved in MS remains unstudied.…”
Section: Discussionmentioning
confidence: 99%